O fazer-se professor em turmas multisseriadas na região de Santa Maria/RS: desenvolvimento profissional e saberes experenciais - Ribas, Juliana da Rosa (2016)
This dissertation is about the make-teacher in multigrade classes in the region of Santa Maria, RS, which aims to investigate how it is doing a teacher in multigrade classes, with emphasis on teacher professional development and working conditions of teachers. The research is anchored in a qualitative approach, based on studies by Bauer andGaskell(2002); by Life Stories methodology with an emphasis on narrative (auto) biographical. As information gathering tools narrative interviews were used (auto) biographical, which provided retell the personal and professional trajectory of collaborators. The theoretical framework was based on authors researching this subject, including Abrahão (2006.2008); Antunes( 2001,2007); Antunes; Ribas (2015), Cardoso; Jacomeli (2010). Damasceno; Bessera (2004); Hage (2010a, 2010b, 2011); Bolzan (2002); Isaia (2001) Molinari (2009); Nóvoa (1992.1995); Ribas; Antunes (2014); Santos (2007); Souza (2006, 2011); Souza; Ferreira (2009). I understand that the development of this research was very important because it enabled us to understand that although many challenges that are found in multigrade schools is through / the experience that teachers have been constructed professionals who believe in the work capability in the face of multigrade classes . There is an urgent need for increased research involving this theme, giving voice to those working in the face of multigrade classes , which have such rich experiences that deserve to be heard and shared with other professionals, because I believe it is a way to not let these schools suffer abandonment, erasing and silencing , and realize as a way to be valuing and believing in the work of professionals and contribute to the deconstruction of the erroneous view that has been among the multisseridas schools.